Felici cvriositate: studies in Latin literature and textual criticism from antiquity to the twentieth century : in honour of Rita Beyers - Guldentops, Guy; Laes, Christian; Partoens, Gert; Beyers, Rita (Instrumenta patristica et mediaevalia, 2017)
The papers collected in this "Festschrift" in honour of Rita Beyers, Professor Emerita of Latin at the University of Antwerp and Director of the "Corpus Christianorum", "Series Latina" and "Continuatio Mediaevalis", focus on ancient (especially Christian) Latin literature and its influence in the Middle Ages and beyond